Experimental Proof-of-Concept of a Spatial Photonic Switch Based on an Off-Axis Zone Plate in Millimeter Wavelength Range - Paulish A. G. Andrey Georgievich; Minin O. V. Oleg Vladilenovich; Geints Yu. E. Yury; Minin I. V. Igor Vladilenovich (2022, 2022)
Title screen